Luxury fashion brands and internet memes as a social media strategy in the context of brand coolness, consumer brand engagement and measures and effects of visual complexity - Silva, Inês Gomes da (2021)
In an era where social networks assume a crucial role in brand strategies, it becomes imperative to study the new communication tools that companies use to differentiate themselves and achieve the intended goals. For their specificities, luxury brands deserve special attention, especially when it comes to the use of more irreverent forms of communication, as is the case of internet memes that have become increasingly popular and part of the online language. Therefore, this study aims to understand how the most luxurious fashion brands can or should incorporate this new type of content in their communication strategy. Therefore, this theme was explored in the context of Brand Coolness, Consumer Brand Engagement and Measures and Effects of Visual Complexity, in which through the chosen research methodology – netnography – were analyzed about 300 internet memes of the collected sample. The results obtained based on the literature of the three aforementioned subjects show that the collected memes do not meet the characteristics that should be expected for luxury brand contents: it was verified that the most relevant dimensions of Brand Coolness are Subcultural, Authentic and Original, and High-Status and Aesthetically Appealing were expected to be among the most important ones. It was also found that the most relevant Engagement dimension is Cognitive and regarding the aesthetic, the contents are not visually harmonious but rather disorganized and complex.